Profile of the life and works of ten Women in Indian film (New Delhi: Zubaan)
Aarti Bajaj, Aparna Sen,Farah khan,Jaya Bachhan,Madhuri Dixit,Mumtas,Nutan,Saira Banu,Smita Patil,Zeenat Aman.
Llife and works of Ten women actress in Indian film
Keywords: Film Actress Biography; Film Studies; Arts